Strategie reżyserskie współczesnych inscenizatorów „wielkiej powieści” – na przykładzie 'Trylogii' Jana Klaty i 'Chłopów' Krzysztofa Garbaczewskiego - Kostaszuk-Romanowska, Monika (Załącznik Kulturoznawczy, 2021)
The great Polish novel is a staging task willingly undertaken by directors. The term ‘great novel’ means a novel in the epic type. The essence of its theatrical potential is already determined by its volume – it is undoubtedly a tempting challenge for the director. Equally inspiring are the basic features of an epic itself – a wide, panoramic spectrum of the community, embedded in the discourse of breakthrough, solstice of ideas, values, and identity identifications. The text discusses five source clues leading to the stage adaptations of the ‘great novel’ – the idea of post-dramatic nature, the issue of theatrical adaptation of a literary work, the issue of the so-called ‘indecency’, the formula of engaged theater and the problem of confrontation between reading the novel with the perceptual order of theatrical staging. The second part of the text presents the producer’s strategies used in two, especially important novels staged in recent years – the Trilogy, directed by Jan Klata and Peasant Farmers directed by Krzysztof Garbaczewski.